Analisis Persepsi dan Strategi Pengawasan Akuntansi Syariah oleh OJK dalam Mencegah Praktik Keuangan Ilegal pada Industri Fintech Syariah di Indonesia - Sabila Zahra; Yusrizal Yusrizal; Waizul Qarni (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the effectiveness of sharia accounting supervision by the Financial Services Authority (OJK) in preventing illegal financial practices in the Islamic fintech industry in Indonesia, as well as to identify the factors influencing public trust, the weaknesses of the supervisory strategy, and strategic recommendations for strengthening governance and consumer protection. This research uses a qualitative descriptive method with primary data from in-depth interviews with an OJK representative in North Sumatra and secondary data from literature studies, regulations, and previous research. The findings indicate that OJK's multi-layer supervision, which includes pre-operational and operational stages as well as coordination with the Sharia Supervisory Board (DPS), is quite effective but still requires improvement in regulatory adaptation speed to keep up with the rapid innovation of illegal fintech actors (regulatory lag). The three dominant factors influencing public trust are information transparency, the track record of fintech organizers, and community experiences. The main weaknesses of supervision are regulatory lag and low reporting rates by victims due to lack of knowledge or fear. Sharia financial literacy is emphasized as the first line of defense, and OJK North Sumatra has actively conducted education programs reaching Islamic boarding schools and religious study groups. This study recommends structured and continuous communication forums among regulators, fintech organizers, and the public, as well as strengthening technology-based reporting systems and empowering the community as part of the supervision mechanism.